English online : a student's guide to the Internet and the World Wide Web - Crump, Eric. (Houghton Mifflin, 1997)
Introduction to the online world. Netiquette. Preparing to enter the Internet. Electronic mail. Mailing lists: hosts for discussion groups and online communities. Telnetting on the Internet. Gopher and Lynx. File transfer protocol...